Ubiquity of organic nitrates from nighttime chemistry in the European submicron aerosol. Issue 14 (30th July 2016) - Kiendler‐Scharr, A.; Mensah, A. A.; Friese, E.; Topping, D.; Nemitz, E.; Prevot, A. S. H.; Äijälä, M.; Allan, J.; Canonaco, F.; Canagaratna, M.; Carbone, S.; Crippa, M.; et al.
Abstract: In the atmosphere nighttime removal of volatile organic compounds is initiated to a large extent by reaction with the nitrate radical (NO3 ) forming organic nitrates which partition between gas and particulate phase. Here we show based on particle phase measurements performed at a suburban site in the Netherlands that organic nitrates contribute substantially to particulate nitrate and organic mass. Comparisons with a chemistry transport model indicate that most of the measured particulate organic nitrates are formed by NO3 oxidation. Using aerosol composition data from three intensive observation periods at numerous measurement sites across Europe, we conclude that organic nitrates are a considerable fraction of fine particulate matter (PM1 ) at the continental scale. Organic nitrates represent 34% to 44% of measured submicron aerosol nitrate and are found at all urban and rural sites, implying a substantial potential of PM reduction by NO x emission control. Key Points: Particulate organic nitrate is ubiquitous in Europe The 34 to 44 percent of fine particulate nitrate is organic Nighttime chemistry is a dominant source of particulate organic nitrates